2005
DOI: 10.1097/01.iop.0000161718.54275.7d
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriology of Chronic Dacryocystitis in a Tertiary Eye Care Center

Abstract: Several bacterial species may be involved in the pathogenesis of chronic dacryocystitis in adults, and the majority of patients harbor multiple microorganisms in their nasolacrimal sacs. The high rate of microorganism-positive lacrimal sac cultures suggests that adult patients should be treated for their infection before any intraocular surgery because of the potential risk of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

11
60
0
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 7 publications
11
60
0
3
Order By: Relevance
“…(9) The overwhelming majority of cases had unilateral affection but overall, both sides were equally affected. This was consistent with the findings of Sood NN et al (13) although some studies (10,14) found more incidence of dacryocystitis on the left side and others (6) on the right side.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…(9) The overwhelming majority of cases had unilateral affection but overall, both sides were equally affected. This was consistent with the findings of Sood NN et al (13) although some studies (10,14) found more incidence of dacryocystitis on the left side and others (6) on the right side.…”
Section: Discussionsupporting
confidence: 83%
“…(8,9) There was a female preponderance with their frequency of affection being almost twice as that of males. This is similar to findings of hospital-based studies in rural India (4) (which found a male-to-female ratio of 1:2.1) and in urban India (6) (which observed it to be 1:2.3), as well as a study from Saudi Arabia (10) . It is also consistent with findings of Shigeta et al (11) who observed that anatomic differences of narrow bony nasolacrimal canal and acute angle between the bony canal and the nasal floor predispose females to primary acquired obstruction of the nasolacrimal system.…”
Section: Discussionsupporting
confidence: 78%
“…25 CDC was associated with Gram-negative bacteria 26% of the time in a study from Saudi Arabia, with one-third of the Gram-negative isolates being H. influenza. 26 The most significant Gram-negative presence has been reported by Briscoe et al, with 61% Gram-negative isolates in patients with purulent dacryocystitis in Israel. 27 In that study, the most common bacterium was P. aeruginosa, accounting for 22% of all isolates (ie, including Gram positive and Gram negative combined).…”
Section: Discussionmentioning
confidence: 82%
“…27 The authors noted frequent resistance of the Gram-negative bacteria to the antibiotic agents routinely selected for empiric therapy in dacryocystitis. 26,27 US data from Mills et al 10 showed a 28.7% prevalence of Gram-negative bacteria, with P. aeruginosa being the most frequent. In the present study, Gram-negative bacteria were found in 74% of the lacrimal systems cultured, with the most frequent being Haemophilus influenzae, followed by P. aeruginosa and P. mirabilis.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of anaerobic culture would be certainly a useful aid in similar studies. The authors wanted to confine the study to the aerobic organism's domain only since anaerobic organisms have a relatively lesser role in chronic dacryocysititis as per the previous studies [8,13].…”
Section: Discussionmentioning
confidence: 99%